2012
DOI: 10.1126/scisignal.2002918
|View full text |Cite
|
Sign up to set email alerts
|

p53 Functions in Endothelial Cells to Prevent Radiation-Induced Myocardial Injury in Mice

Abstract: p53 functions in the heart to promote myocardial injury after multiple types of stress. However, how p53 regulates radiation-induced myocardial injury, which develops after radiation therapy, is not well understood. Here, we utilize the Cre-loxP system to demonstrate that p53 functioned in endothelial cells to protect mice from myocardial injury after whole-heart irradiation. Mice with an endothelial cell-specific deletion of p53 succumbed to heart failure after whole-heart irradiation due to myocardial necros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 65 publications
3
87
0
Order By: Relevance
“…Recently, we reported that cardiac endothelial cells lacking p53 or p21 are sensitized to radiation (11). Furthermore, mice lacking p21 or mice lacking p53 specifically in endothelial cells were sensitized to radiation-induced myocardial necrosis (11). Here, we found that deletion of p53 in endothelial cells not only permitted Atm deletion to sensitize endothelial cells to radiation in vitro, but also allowed Atm deletion to accelerate radiation-induced myocardial necrosis in vivo.…”
Section: Loss Of Atm Sensitizes Proliferating But Not Quiescent Endmentioning
confidence: 51%
See 3 more Smart Citations
“…Recently, we reported that cardiac endothelial cells lacking p53 or p21 are sensitized to radiation (11). Furthermore, mice lacking p21 or mice lacking p53 specifically in endothelial cells were sensitized to radiation-induced myocardial necrosis (11). Here, we found that deletion of p53 in endothelial cells not only permitted Atm deletion to sensitize endothelial cells to radiation in vitro, but also allowed Atm deletion to accelerate radiation-induced myocardial necrosis in vivo.…”
Section: Loss Of Atm Sensitizes Proliferating But Not Quiescent Endmentioning
confidence: 51%
“…Our present results suggested that the abrogation of cell cycle checkpoints allows quiescent cells to be sensitized to radiation as a consequence of Atm deletion. Recently, we reported that cardiac endothelial cells lacking p53 or p21 are sensitized to radiation (11). Furthermore, mice lacking p21 or mice lacking p53 specifically in endothelial cells were sensitized to radiation-induced myocardial necrosis (11).…”
Section: Loss Of Atm Sensitizes Proliferating But Not Quiescent Endmentioning
confidence: 99%
See 2 more Smart Citations
“…Whole-heart 12 Gy irradiation led to impaired systolic function, cardiac hypertrophy, vascular remodeling, myocardial hypoxia, necrosis and ischemia. Mice lacking p21, a transcriptional target of p53, also developed myocardial degeneration, necrosis, systolic dysfunction and cardiac hypertrophy after whole-heart 12 Gy irradiation (66).…”
Section: Animal Studiesmentioning
confidence: 99%